Effluent Treatment System for Low Loads – Biodigester: Case Study - da Costa, Pedro Carlos Lemos; Silva Martins, Fabiano Battemarco da; Rodrigues da Nóbrega, Marcelo de Jesus; Junior, Luiz Affonso de Paula (International Journal of Advanced Engineering Research and Science, 2022)
Water is an extremely important resource for the maintenance of life on earth and several human activities depend on it for its development, such as: agricultural production, industrial activities and energy generation. It is estimated that in a short time this resource, which has already been considered renewable, will be the object of conflict between nations. In order to be able to continue enjoying this asset, measures are needed to maintain the quality of water sources, such as the proper treatment of sanitary sewage for the discharge of water bodies. In this context, the present work aims to present a low load sanitary effluent treatment equipment that can be adopted in homes and industries, the Biodigester by the FIBROMAR company. This equipment has 03 chambers, where the first two work as an RAFA (Ascending Flow Anaerobic Reactor) and the last as an Anaerobic Filter. It was installed for evaluation in an industrial shed receiving the contribution of 10 people during business hours, where in 2015, after 06 months of use, the analyzes performed showed efficiency values in the removal of 87% DBO (61.00 mg/l) and final concentration of RNFT 25.00 mg/l efficiency of the equipment to meet CONAMA No. 430/11 (supplementary No. 357/05) and NT-202-R10 (INEA-RJ). Recently in 2021, the analyzes were repeated to evaluate the system's functioning, the results showed DBO removal efficiency 93% (8.00 mg/l) and Total Suspended Solids less than 10 mg/l, remaining within the parameters of legislation previously evaluated and in line with recent legislation (NOP 45 – CONEMA 90).